Electrochemically active biofilm-enabled biosensors: current status and opportunities for biofilm engineering - Hu, Yidan (2022)
Electrochemically active biofilms (EABs) are formed by electroactive bacteria capable of exchanging electrons with electrodes. EABs have been employed as bio-elements in bioelectrochemical sensors which sense analytes of interest by converting metabolic changes to easily detectable electrical signals. Although EAB-enabled biosensors have shown promise in environmental applications, such as water quality monitoring, their most perceived practical applications are limited by low sensitivity, low specificity and short-term stability. Engineering EABs could be an effective strategy to improve the performance of EAB-enabled biosensors. In this review, we briefly introduce EAB with the focus on its extracellular electron transfer, development and matrix, as well as EAB-enabled biosensors including their general principle and potential applications. We then discuss key limitations of EAB-enabled biosensors and the opportunities that biofilm engineering may provide to address these limitations.